Manifestation Of Prophetic Leadership Values In Islamic Education - Try Heni Aprilia; Munifah Munifah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
The issue of morality is still a hot issue that is still being discussed. The flow of globalization has resulted in the erosion of human morality so that it only prioritizes the capitalist and materialistic aspects. Educational institutions as the main basis of human civilization and intellectuality should be able to become a place for transmitting moral values that are always based on prophethood and divinity. In reviewing the problems above, this study uses a library research approach with data analysis methods, content analysis, and spiral analysis. The findings of this study are that prophetic leadership is a leadership typology that is oriented towards restoring human nature as caliphs on earth by making the prophet Muhammad a role model in carrying out his leadership activities. Prophetic Islamic education is also an effort to prevent moral degradation because it returns the function of education to a divine basis, and always has high faith so that it can create a generation of rahmatan lil-‘alamin. These prophetic leadership values are inspired by Kuntowijoyo’s ‘social prophetic’ concept, including humanists, liberals, and transcendentals.